Multimessenger Binary Mergers Containing Neutron Stars: Gravitational Waves, Jets, and γ-Ray Bursts - Ruiz, Milton; Shapiro, Stuart L.; Tsokaros, Antonios (Frontiers in Astronomy and Space Sciences, 2021)
Neutron stars (NSs) are extraordinary not only because they are the densest form of matter in the visible Universe but also because they can generate magnetic fields ten orders of magnitude larger than those currently constructed on Earth. The combination of extreme gravity with the enormous electromagnetic (EM) fields gives rise to spectacular phenomena like those observed on August 2017 with the merger of a binary neutron star system, an event that generated a gravitational wave (GW) signal, a short $γ$-ray burst (sGRB), and a kilonova. This event serves as the highlight so far of the era of multimessenger astronomy. In this review, we present the current state of our theoretical understanding of compact binary mergers containing NSs as gleaned from the latest general relativistic magnetohydrodynamic simulations. Such mergers can lead to events like the one on August 2017, GW170817, and its EM counterparts, GRB 170817 and AT 2017gfo. In addition to exploring the GW emission from binary black hole-neutron star and neutron star-neutron star mergers, we also focus on their counterpart EM signals. In particular, we are interested in identifying the conditions under which a relativistic jet can be launched following these mergers. Such a jet is an essential feature of most sGRB models and provides the main conduit of energy from the central object to the outer radiation regions. Jet properties, including their lifetimes and Poynting luminosities, the effects of the initial magnetic field geometries and spins of the coalescing NSs, as well as their governing equation of state, are discussed. Lastly, we present our current understanding of how the Blandford-Znajek mechanism arises from merger remnants as the trigger for launching jets, if, when and how a horizon is necessary for this mechanism, and the possibility that it can turn on in magnetized neutron ergostars, which contain ergoregions, but no horizons.